Bianchi type-VI0 cosmological models with isotropic dark energy - Chandel S.; Singh M.K.; Ram S. (My University, 2025)
We present spatially homogeneous and anisotropic Bianchi-type VI0 cosmological models of the universe filled with dark energy in general theory of relativity. The Einstein's field equations have been solved exactly with the assumption that the shear scalar is proportional to the expansion scalar, which for some suitable choices of problem parameters, yield singular and non-singular dark energy models of the universe. The physical and kinematical behaviors of the models are discussed. We conclude that the universe models do not approach isotropy through the future evolution of the universe. © Electronic Journal of Theoretical Physics.